2020
DOI: 10.1302/0301-620x.102b5.bjj-2019-1385.r1
|View full text |Cite
|
Sign up to set email alerts
|

Patient function continues to improve over the first five years following tibial plateau fracture managed by open reduction and internal fixation

Abstract: Aims Tibial plateau fractures are serious injuries about the knee that have the potential to affect patients’ long-term function. To our knowledge, this is the first study to use patient-reported outcomes (PROs) with a musculoskeletal focus to assess the long-term outcome, as compared to a short-term outcome baseline, of tibial plateau fractures treated using modern techniques. Methods In total, 102 patients who sustained a displaced tibial plateau fracture and underwent operative repair by one of three orthop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…We found no differences in the range of motion between the intervention and control groups overall and between the ankle and tibial plateau fracture subgroups, our results are in line with other studies that reported the range of motion of the ankle and knee. [32][33][34][35][36] Our findings should be interpreted within the limitations of this study. The main limitation was the significant proportion of patients who dropped out.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…We found no differences in the range of motion between the intervention and control groups overall and between the ankle and tibial plateau fracture subgroups, our results are in line with other studies that reported the range of motion of the ankle and knee. [32][33][34][35][36] Our findings should be interpreted within the limitations of this study. The main limitation was the significant proportion of patients who dropped out.…”
Section: Discussionmentioning
confidence: 74%
“…We found no differences in the range of motion between the intervention and control groups overall and between the ankle and tibial plateau fracture subgroups, our results are in line with other studies that reported the range of motion of the ankle and knee. 3236…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of functional outcomes following TPF specifically have used a number of different PROMs. Gonzalez et al 19 reported Short Musculoskeletal Functional Assessment (SMFA) scores at one and > five years in 138 patients with operatively managed TPFs. They reported a statistically significant improvement in mean scores in all SMFA domains except pain from one- to > five-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Foot and Ankle Ability Measure median score was 74% of full function, which is similar to our results using PROMIS PF. Comparative literature in other lower extremity fractures is sparce, but Gonzalez et al 10 published on 1- and 5-year outcomes of tibial plateau fractures showing continued improvement throughout the time frame. This suggests that there is likely differences in the recovery of various lower extremity fractures that deserves further investigation.…”
Section: Discussionmentioning
confidence: 99%